Mercury mobility in a salt marsh colonised by Halimione portulacoides - Valega, M. (2008)
The present study intends to increase the knowledge on the mobility of mercury in a salt marsh colonised by Halimione portulacoides. Mercury distribution in the sediment layers and its incorporation into the plant biomass were assessed, as well as the potential export of mercury from the contaminated area to the adjacent environment. Mercury pools in the sediments ranged from 560 to 943 mg m−2 and are largely associated with the solid fraction, with just a small amount being associated with the pore waters. Estimated diffusive fluxes of reactive mercury ranged from 1.3 to 103 ng m−2 d−1. Despite the above ground biomass values being comparatively higher than below ground biomass values, the mercury pools were much higher in the root system (0.06–0.16 mg m−2 and 29–102 mg m−2, respectively). The annual bioaccumulation of mercury in above ground tissues was estimated in 0.11 mg m−2 y−1, while in below ground biomass the values were higher (72 mg m−2 y−1). The turnover rates of H. portulacoides biomass suggest higher mercury mobility within the plant rhizosphere. Taking into account the pools of mercury in above ground biomass, the export of mercury by macro-detritus following the “outwelling hypothesis” is not significant for the mercury balance in the studied ecosystem. The mercury accumulated in the below ground part of the plant is quite mobile, being able to return to the sediment pool throughout the mineralisation process.